Diastolic Dysfunction in Liver Cirrhosis: Prognostic Predictor in Liver Transplantation? - Carvalheiro, F (2016)
BACKGROUND: Patients with liver cirrhosis may develop cirrhotic cardiomyopathy (CC), characterized by blunted contractile responsiveness to stress, diastolic dysfunction (DD), and electrophysiological abnormalities. It may adversely affect the long-term prognosis of these patients. METHODS: We conducted a retrospective analysis of patients undergoing liver transplantation (LT) for cirrhosis from January 2012 to June 2015. We analyzed demographic characteristics, the etiology of cirrhosis, Child-Pugh and Model for End-Stage Liver Disease (MELD) scores, the corrected QT (QTc) interval in the preoperative period, diastolic and systolic dysfunction, mortality and survival, and duration of mechanical ventilation and vasopressor support in the post-LT period. These variables were compared with diastolic dysfunction and prolongation of QTc, with the use of chi-square, Fisher, and Mann-Whitney U tests. RESULTS: The study included 106 patients, 80.2% male and overall average age 54.83 years. The median MELD score was 16, and Child-Pugh class C in 55.4%. Prolonged QTc interval before LT was present in 19% and DD in 35.8% of patients. QTc before LT or DD did not vary significantly with MELD or Child-Pugh score. CONCLUSIONS: The patients in the pre-LT period presented with a significant incidence of DD, which can predispose them to adverse cardiac events. The presence of DD correlates with mortality after LT in patients with hepatic cirrhosis.